Driving Growth: The Role of Digitalization in Indonesia’s Economy - Anggraini, Radella; Anindyntha, Firdha Aksari (Jurnal Samudra Ekonomi dan Bisnis, 2025)
Economic digitalization has transformed various aspects of economic activities and plays a pivotal role in shaping the dynamic economic landscape of Indonesia. This study examines the impact of digitalization on Indonesia’s economic growth from 2019 to 2023, measured through internet access, mobile phone ownership, e-commerce usage, and the ICT Index. Using panel regression analysis, the results show that internet access and mobile phone ownership significantly and positively affect economic growth, highlighting the importance of digital connectivity in boosting national productivity and economic efficiency. Conversely, e-commerce usage and the ICT Index have a significant negative impact, possibly due to unequal access, dominance of imported goods, and suboptimal digital infrastructure. These findings emphasize that digital transformation must be supported by equitable infrastructure distribution, improved access to technology, enhanced digital literacy, and adaptive government policies to drive sustainable and inclusive growth across Indonesia.